Pharmaceutical wastewater treatment process
Through the combined process of composite adsorbent and gel microsphere oxidizing agent, the problem of heavy metal removal in pharmaceutical wastewater is solved, and efficient and stable wastewater treatment effect is achieved, ensuring that the effluent meets the standards and extending the service life of the adsorbent.
Patent Information
- Application Number
- CN202510918905.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-04
- Publication Date
- 2025-09-02
AI Technical Summary
The existing pharmaceutical wastewater treatment process is difficult to effectively remove heavy metal ions, resulting in the possibility of re-releasing of wastewater into the environment after treatment, causing secondary pollution.
The combined process of composite adsorbent and gel microsphere oxidant is adopted, including pretreatment, adsorption, oxidation and filtration, and the synergistic effect of modified nano zero-valent iron and gel microsphere oxidant is achieved through dynamic chemical bonds.
It significantly improves the removal capacity of organic matter and heavy metals, ensures that the effluent meets the standards, extends the service life of the adsorbent, and achieves efficient degradation and purification through multiple mechanisms.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of wastewater treatment, in particular to a pharmaceutical wastewater treatment process. Background Art
[0002] The pharmaceutical industry, a vital industry crucial to national economy and people's livelihood, plays a key role in safeguarding human health. However, pharmaceutical production processes generate large quantities of wastewater with complex compositions and high levels of pollution. This wastewater often contains harmful substances such as antibiotics, hormones, organic solvents, heavy metals, and high concentrations of organic pollutants. It also exhibits characteristics such as high COD (chemical oxygen demand), high ammonia nitrogen, high salinity, and poor biodegradability. Common pharmaceutical wastewater treatment methods include physical, chemical, and biological treatment. While physical treatment methods such as adsorption and precipitation can remove some suspended solids and macromolecular organic matter, they are limited in their removal of dissolved organic matter and toxic substances. Chemical treatment methods such as advanced oxidation technology, while effective in degrading poorly biodegradable organic matter, are associated with high reagent consumption, high treatment costs, and the potential for secondary pollution. Biological treatment, while currently the most widely used treatment method, has high requirements for influent water quality. When treating high-salinity and highly toxic pharmaceutical wastewater, microbial activity is easily suppressed, resulting in low treatment efficiency.
[0003] In the related art, the patent application document with publication number CN103739147A discloses a pharmaceutical wastewater treatment process, which includes high-concentration wastewater and low-concentration wastewater, wherein: the high-concentration pharmaceutical wastewater passes through the Fenton catalytic oxidation reaction tank to undergo Fenton reaction and then enters the high-efficiency sedimentation tank; the low-concentration pharmaceutical wastewater enters the regulating tank together with the effluent from the high-efficiency sedimentation tank, and is pumped to the hydrolysis and acidification tank. Through the action of anaerobic microorganisms, organic matter is removed and suspended solids in the water are reduced. The effluent from the hydrolysis and acidification tank flows into the CASS tank, and the effluent from the CASS tank meets the discharge standards; the sludge generated by the high-efficiency sedimentation tank, hydrolysis and acidification tank, and CASS tank is discharged into the sludge thickening tank, and the dry sludge is transported for disposal after passing through a chamber filter press. The pharmaceutical wastewater treatment process in the above scheme has the advantages of simple process and stable properties.
[0004] In actual operation, the above-mentioned wastewater treatment process only treats wastewater through conventional treatment units such as Fenton catalytic oxidation, precipitation, hydrolysis acidification, and CASS tanks. These units mainly target organic matter and suspended solids, and do not have a specific process step for removing heavy metal ions. Pharmaceutical wastewater usually contains a large amount of heavy metal ions, mainly copper and chromium. Although the Fenton reaction can oxidize organic matter, it has a weak effect on removing heavy metal ions; high-efficiency sedimentation tanks rely on coagulation and sedimentation to remove some suspended matter, and it is difficult to effectively remove dissolved heavy metal ions; hydrolysis acidification and CASS tanks mainly use microorganisms to treat organic matter, and the microorganisms have limited ability to adsorb and transform heavy metals, and cannot ensure that heavy metal ions meet standards. Therefore, heavy metals in treated pharmaceutical wastewater may still be released back into the environment, causing secondary pollution. Summary of the Invention
[0005] In view of this, the present invention proposes a pharmaceutical wastewater treatment process to solve the above problems.
[0006] The technical solution of the present invention is achieved as follows:
[0007] A pharmaceutical wastewater treatment process comprises the following steps:
[0008] A1. Pretreatment: Pharmaceutical wastewater is introduced into a regulating tank and adjusted to a pH of 5.0-6.0. The regulated wastewater then enters a coagulation and sedimentation tank. After adding a coagulant, the wastewater is aerated and stirred for 2-3 hours, and then allowed to settle for 18-24 hours.
[0009] A2. Adsorption: The pretreated supernatant was passed through a fixed-bed reactor filled with a composite adsorbent at a flow rate of 4-5 L / min for adsorption. The composite adsorbent ingredients included attapulgite, activated carbon, carbon nanotubes, starch, sodium dithiocarbamate, 4-carboxyphenylboronic acid, epoxy resin E-44, polyethyleneimine, modified nano-zero-valent iron, and deionized water.
[0010] A3. Oxidation treatment: The wastewater after adsorption treatment is passed into the oxidation tank, and the gel microsphere oxidant is added at a dosage of 200-300 mg / L. The aeration reaction is carried out for 1-2 hours;
[0011] A4. Filtration treatment: The wastewater after oxidation treatment is filtered through an activated carbon filter with a residence time of 15-30 minutes to obtain purified water.
[0012] Furthermore, the coagulant described in A1 is composed of polyaluminum chloride and aluminum sulfate in a mass ratio of (5-7):(3-5).
[0013] Furthermore, the regulator for regulating the pH of pharmaceutical wastewater in A1 is a hydrochloric acid solution with a mass concentration of 10-20 wt%.
[0014] Furthermore, the composite adsorbent in A2 comprises the following raw materials in parts by weight: 40-60 parts of attapulgite, 20-30 parts of activated carbon, 5-10 parts of carbon nanotubes, 2-5 parts of starch, 10-15 parts of 4-carboxyphenylboric acid, 20-30 parts of polyethyleneimine, 5-8 parts of sodium dithiocarbamate, 5 parts of epoxy resin E-443, 50-80 parts of deionized water, and 10-15 parts of modified nano zero-valent iron;
[0015] The modified nano zero-valent iron is obtained by chemically bonding polyethyleneimine onto the nano zero-valent iron.
[0016] Furthermore, modified nano-zero-valent iron was prepared by the following method: nano-zero-valent iron was dispersed in anhydrous ethanol, ultrasonically treated for 10-20 minutes under ultrasonic power of 100-300W and ultrasonic frequency of 20-40kHz, and then polyethyleneimine solution was added, stirred and reacted at 30-50°C for 1-2 hours, and the modified nano-zero-valent iron was obtained after filtering, washing, and drying.
[0017] Furthermore, the mass volume ratio of nano zero-valent iron to anhydrous ethanol is 1:(5-8) g / mL, the mass concentration of the polyethyleneimine solution is 3-5wt%; and the mass volume ratio of the polyethyleneimine solution added to the nano zero-valent iron is 1:2-3 g / mL.
[0018] Furthermore, the composite adsorbent is prepared by the following method:
[0019] B1. The attapulgite, activated carbon, carbon nanotubes and starch were mixed and granulated by spray drying and calcined at 500-600 ℃ for 2-3h to obtain a carrier material;
[0020] B2. 4-carboxyphenylboronic acid was dissolved in ethanol to obtain a 4-carboxyphenylboronic acid solution; the support material was immersed in the 4-carboxyphenylboronic acid solution, stirred at 55-65 ° C for 4-6h, followed by the addition of sodium dithiocarbamate, stirred at 70-80 ° C for 1.5-2.5h, filtered and washed to obtain an activated support;
[0021] B3. Pre-react polyethyleneimine with epoxy resin E-44 at 48-52 ° C for 1-1.5h to obtain an imine bond prepolymer;
[0022] B4. The imine bond prepolymer is coated onto the activated support and cured at 75-85°C for 2-3h;
[0023] B5. Disperse the modified nano-zero-valent iron in deionized water to obtain a dispersion, then immerse the activated support in the dispersion. Oscillate and adsorb at room temperature for 2.5-3.5 hours. After filtration and separation, the solid product is dried at 60-80°C for 4-6 hours to obtain a composite adsorbent.
[0024] Furthermore, the gel microsphere oxidant described in A3 comprises the following raw materials in parts by weight: 50-60 parts of hydrogen peroxide, 20-25 parts of potassium persulfate, 10-15 parts of copper iron sulfide, 4-8 parts of nitrogen-doped carbon quantum dots, 8-12 parts of sodium alginate powder, 0.5-1 part of sodium polyacrylate, and 0.8-1.2 parts of phosphate buffer.
[0025] Furthermore, the gel microsphere oxidant is prepared by the following method:
[0026] C1. Under a nitrogen atmosphere, copper iron sulfide and nitrogen-doped carbon quantum dots were added to hydrogen peroxide precooled to 8-12°C. The mixture was ultrasonically dispersed at 34-36°C for 15-20 minutes. Phosphate buffer was added and stirred for 4-6 minutes to obtain suspension I.
[0027] C2. Sodium alginate powder was added to suspension I, stirred at 40°C at 140-160 rpm for 25-30 min, then heated to 45°C at 75-85 rpm for 25-30 min, cooled to 30-32°C, potassium persulfate was added, and magnetic stirring was performed until completely dissolved to obtain a viscous slurry II;
[0028] C3. The viscous slurry II was injected into a ball dropper, and 2 wt% calcium chloride solution was added dropwise. The mixture was cured for 20-30 min to obtain microspheres. The microspheres were filtered out, washed with deionized water, and then freeze-dried to obtain a gel microsphere oxidant.
[0029] Furthermore, in C1, the ultrasonic power is 200-400 W, the ultrasonic frequency is 15-25 kHz, and the stirring speed is 150-250 rpm; in C2, the magnetic stirring speed is 300-500 rpm; and in C3, the freeze-drying temperature is -30 to -40°C, and the drying time is 24-36 h.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1. The composite adsorbent of this invention achieves self-repair through dynamic chemical bonds, such as borate ester bonds, imine bonds, and thiol-disulfide bonds, thereby maintaining a high adsorption capacity and extending the adsorbent's service life. Modified nano-zero-valent iron generates precipitates such as FeO(OH) through reduction, filling surface cracks and inhibiting metal corrosion. The modified nano-zero-valent iron not only provides electrons to accelerate dynamic bond recombination but also provides a space-filling effect to prevent crack propagation, achieving an integrated "catalysis-repair" design.
[0032] 2. The gel microsphere oxidant of the present invention achieves efficient degradation through the synergistic mechanism of free radical oxidation + non-free radical oxidation + photocatalysis.
[0033] 3. The present invention uses the cascade effect of pretreatment-oxidation-filtration to remove suspended matter by coagulation and sedimentation, reduce subsequent loads, use composite adsorbents to remove difficult-to-degrade organic matter and heavy metals in a targeted manner, perform oxidation treatment to deeply mineralize residual pollutants, and filter out residual trace difficult-to-degrade organic matter and remove color and odor substances to ensure that the effluent meets the standards. DETAILED DESCRIPTION
[0034] In order to better understand the technical content of the present invention, specific examples are provided below to further illustrate the present invention.
[0035] Unless otherwise specified, the experimental methods used in the examples of the present invention are all conventional methods.
[0036] Unless otherwise specified, the materials, reagents, etc. used in the examples of the present invention can be obtained from commercial sources.
[0037] Example 1
[0038] A pharmaceutical wastewater treatment process comprises the following steps:
[0039] A1. Pretreatment: Pharmaceutical wastewater is introduced into a regulating tank and adjusted to a pH of 5.0. The regulated wastewater then enters a coagulation and sedimentation tank. After the addition of a coagulant, the mixture is aerated and stirred for 2 hours, followed by 18 hours of settling. The coagulant consists of polyaluminum chloride and aluminum sulfate in a mass ratio of 5:3. The pH regulator used to adjust the pharmaceutical wastewater is a 20wt% hydrochloric acid solution.
[0040] A2. Adsorption treatment: The pretreated supernatant is passed into a fixed-bed reactor filled with a composite adsorbent for adsorption reaction at a flow rate of 4 L / min. When the pressure difference reaches 15%, the water inlet valve is closed, the residual wastewater is drained, and 70°C hot water is reversely passed from the bottom of the reactor at a flow rate of 8 L / min for 30 minutes. After the end, it is switched to room temperature deionized water for 15 minutes, and then the water supply is restored for the next adsorption cycle. Among them, the composite adsorbent includes the following raw materials in parts by weight: 40 parts of attapulgite, 20 parts of activated carbon, 5 parts of carbon nanotubes, 2 parts of starch, 10 parts of 4-carboxyphenylboric acid, 20 parts of polyethyleneimine, 5 parts of sodium dithiocarbamate, 3 parts of epoxy resin E-44, 50 parts of deionized water, and 10 parts of modified nano zero-valent iron.
[0041] A3. Oxidation Treatment: Pass the adsorption-treated wastewater into an oxidation tank and add 200 mg / L of gel microsphere oxidant. Aeration reaction is allowed for 2 hours. The gel microsphere oxidant comprises the following ingredients by weight: 50 parts hydrogen peroxide, 20 parts potassium persulfate, 10 parts copper iron sulfide, 4 parts nitrogen-doped carbon quantum dots, 8 parts sodium alginate powder, 0.5 parts sodium polyacrylate, and 0.8 parts phosphate buffer.
[0042] A4. Filtration treatment: The wastewater after oxidation treatment is filtered through an activated carbon filter with a residence time of 15 minutes to obtain purified water.
[0043] The modified nano-zero-valent iron (NPZI) is chemically coated with polyethyleneimine. The process involves dispersing the NPZI in anhydrous ethanol and ultrasonically treating it for 20 minutes at 100W and 200kHz. The NPZI solution is then added, stirred at 30°C for 2 hours, and filtered, washed, and dried to yield the modified NPZI. The weight-to-volume ratio of the NPZI to the ethanol is 1:5 (g / mL), and the concentration of the NPZI solution is 5wt%. The weight-to-volume ratio of the NPZI to the NPZI is 1:2 (g / mL).
[0044] The composite adsorbent is prepared by the following method:
[0045] B1. Attapulgite, activated carbon, carbon nanotubes, and starch were mixed and granulated by spray drying, and then calcined at 500°C for 3h to obtain a carrier material.
[0046] B2. Dissolve 4-carboxyphenylboronic acid in ethanol to obtain a 4-carboxyphenylboronic acid solution; immerse the support material in the 4-carboxyphenylboronic acid solution, stir and react at 55°C for 6 hours, then add sodium dithiocarbamate, stir and react at 70°C for 2.5 hours, filter, and wash to obtain an activated support.
[0047] B3. Pre-react polyethyleneimine with epoxy resin E-44 at 48°C for 1.5 h to obtain an imine bond prepolymer.
[0048] B4. Coat the imine bond prepolymer onto the activated support and cure at 75°C for 3h.
[0049] B5. The modified nano-zero-valent iron was dispersed in deionized water to obtain a dispersion, and then the activated support was immersed in the dispersion. The mixture was oscillated and adsorbed at room temperature for 2.5 h. After filtration and separation, the solid product was dried at 60°C for 6 h to obtain a composite adsorbent.
[0050] The gel microsphere oxidant is prepared by the following method:
[0051] C1. Under a nitrogen atmosphere, copper iron sulfide and nitrogen-doped carbon quantum dots were added to hydrogen peroxide precooled to 8°C. The mixture was ultrasonically dispersed at 34°C with an ultrasonic power of 200 W and an ultrasonic frequency of 15 kHz for 20 min. Phosphate buffer was added and stirred at 150 rpm for 6 min to obtain suspension I.
[0052] C2. Sodium alginate powder was added to suspension I, stirred at 140 rpm at 40°C for 30 min, then heated to 45°C and stirred at 75 rpm for 30 min. Potassium persulfate was added after cooling to 30°C, and magnetic stirring was performed at 300 rpm until completely dissolved to obtain viscous slurry II.
[0053] C3. The viscous slurry II was injected into a ball dropper, and a 2 wt% calcium chloride solution was added dropwise. The mixture was cured for 20 min to obtain microspheres. The microspheres were filtered out, washed with deionized water, and then freeze-dried at -30°C for 36 h to obtain a gel microsphere oxidant.
[0054] Example 2
[0055] A pharmaceutical wastewater treatment process comprises the following steps:
[0056] A1. Pretreatment: Pharmaceutical wastewater is introduced into a regulating tank and adjusted to a pH of 5.5. The regulated wastewater then enters a coagulation and sedimentation tank. After the addition of a coagulant, the mixture is aerated and stirred for 2.5 hours, followed by 21 hours of static sedimentation. The coagulant consists of polyaluminum chloride and aluminum sulfate in a mass ratio of 6:4. The pH regulator used to adjust the pharmaceutical wastewater is a 15wt% hydrochloric acid solution.
[0057] A2. Adsorption treatment: The pretreated supernatant is passed into a fixed bed reactor filled with a composite adsorbent for adsorption reaction at a flow rate of 4.5L / min. When the pressure difference reaches 15%, the water inlet valve is closed, the residual wastewater is emptied, and 75°C hot water is reversely passed from the bottom of the reactor at a flow rate of 9L / min for 30 minutes. After the end, it is switched to room temperature deionized water for 15 minutes, and then the water supply is restored for the next adsorption cycle. Among them, the composite adsorbent includes the following raw materials by weight: 50 parts of attapulgite, 25 parts of activated carbon, 7.5 parts of carbon nanotubes, 3.5 parts of starch, 12.5 parts of 4-carboxyphenylboric acid, 25 parts of polyethyleneimine, 6.5 parts of sodium dithiocarbamate, 44 parts of epoxy resin E-4, 65 parts of deionized water, and 12.5 parts of modified nano zero-valent iron.
[0058] A3. Oxidation Treatment: Pass the adsorption-treated wastewater into an oxidation tank and add 250 mg / L of gel microsphere oxidant. Aeration reaction is carried out for 1.5 hours. The gel microsphere oxidant comprises the following raw materials by weight: 55 parts hydrogen peroxide, 22.5 parts potassium persulfate, 12.5 parts copper iron sulfide, 6 parts nitrogen-doped carbon quantum dots, 10 parts sodium alginate powder, 0.8 parts sodium polyacrylate, and 1 part phosphate buffer.
[0059] A4. Filtration treatment: The wastewater after oxidation treatment is filtered through an activated carbon filter with a residence time of 22 minutes to obtain purified water.
[0060] The modified nano-zero-valent iron (NPZI) is chemically coated with polyethyleneimine. The process involves dispersing the NPZI in anhydrous ethanol and ultrasonically treating it for 15 minutes at 200W and 30kHz. The NPZI solution is then added and stirred at 40°C for 1.5 hours. The mixture is then filtered, washed, and dried to yield the modified NPZI. The weight-to-volume ratio of the NPZI to the ethanol is 1:6.5 (g / mL). The concentration of the NPZI solution is 4wt%. The weight-to-volume ratio of the NPZI to the NPZI is 1:2.5 (g / mL).
[0061] The composite adsorbent is prepared by the following method:
[0062] B1. Attapulgite, activated carbon, carbon nanotubes, and starch were mixed and granulated by spray drying, and then calcined at 550°C for 2.5h to obtain a carrier material.
[0063] B2. Dissolve 4-carboxyphenylboronic acid in ethanol to obtain a 4-carboxyphenylboronic acid solution; immerse the support material in the 4-carboxyphenylboronic acid solution, stir and react at 60°C for 5 hours, then add sodium dithiocarbamate, stir and react at 75°C for 2.0 hours, filter, and wash to obtain an activated support.
[0064] B3. Pre-react polyethyleneimine with epoxy resin E-44 at 50°C for 1.2 h to obtain an imine bond prepolymer.
[0065] B4. Coat the imine bond prepolymer onto the activated support and cure at 80°C for 2.5h.
[0066] B5. The modified nano-zero-valent iron was dispersed in deionized water to obtain a dispersion, and then the activated carrier was immersed in the dispersion. The mixture was oscillated and adsorbed at room temperature for 3.0 h. After filtration and separation, the solid product was dried at 70°C for 5 h to obtain a composite adsorbent.
[0067] The gel microsphere oxidant is prepared by the following method:
[0068] C1. Under a nitrogen atmosphere, copper iron sulfide and nitrogen-doped carbon quantum dots were added to hydrogen peroxide precooled to 10°C. The mixture was ultrasonically dispersed at 35°C with an ultrasonic power of 300 W and an ultrasonic frequency of 20 kHz for 18 min. Phosphate buffer was added and stirred at 200 rpm for 5 min to obtain suspension I.
[0069] C2. Sodium alginate powder was added to suspension I, stirred at 150 rpm at 40°C for 27 min, then heated to 45°C and stirred at 80 rpm for 27 min, cooled to 31°C, potassium persulfate was added, and magnetic stirring was performed at 400 rpm until completely dissolved to obtain viscous slurry II.
[0070] C3. The viscous slurry II was injected into a ball dropper, and a 2 wt % calcium chloride solution was added dropwise. The mixture was cured for 25 min to obtain microspheres. The microspheres were filtered out, washed with deionized water, and then freeze-dried at -35°C for 30 h to obtain a gel microsphere oxidant.
[0071] Example 3
[0072] A pharmaceutical wastewater treatment process comprises the following steps:
[0073] A1. Pretreatment: Pharmaceutical wastewater is introduced into a regulating tank and adjusted to a pH of 6.0. The regulated wastewater then enters a coagulation and sedimentation tank, where a coagulant is added, aerated and stirred for 2 hours, and then allowed to settle for 24 hours. The coagulant consists of polyaluminum chloride and aluminum sulfate in a mass ratio of 7:5. The pH regulator used to adjust the pharmaceutical wastewater is a 10wt% hydrochloric acid solution.
[0074] A2. Adsorption treatment: The pretreated supernatant is passed into a fixed-bed reactor filled with a composite adsorbent for adsorption reaction at a flow rate of 5L / min. When the pressure difference reaches 15%, the water inlet valve is closed, the residual wastewater is emptied, and 80°C hot water is reversely passed from the bottom of the reactor at a flow rate of 10L / min for 30 minutes. After the end, it is switched to room temperature deionized water for rinsing for 15 minutes, and then the water supply is restored for the next adsorption cycle. Among them, the composite adsorbent includes the following raw materials by weight: 60 parts of attapulgite, 30 parts of activated carbon, 10 parts of carbon nanotubes, 5 parts of starch, 15 parts of 4-carboxyphenylboric acid, 30 parts of polyethyleneimine, 8 parts of sodium dithiocarbamate, 5 parts of epoxy resin E-44, 80 parts of deionized water, and 15 parts of modified nano zero-valent iron.
[0075] A3. Oxidation Treatment: Pass the adsorption-treated wastewater into an oxidation tank and add 300 mg / L of gel microsphere oxidant. Aeration reaction is allowed for 1 hour. The gel microsphere oxidant comprises the following ingredients by weight: 60 parts hydrogen peroxide, 25 parts potassium persulfate, 15 parts copper iron sulfide, 8 parts nitrogen-doped carbon quantum dots, 12 parts sodium alginate powder, 1 part sodium polyacrylate, and 1.2 parts phosphate buffer.
[0076] A4. Filtration treatment: The wastewater after oxidation treatment is filtered through an activated carbon filter with a residence time of 30 minutes to obtain purified water.
[0077] The modified nano-zero-valent iron (NPZI) is chemically coated with polyethyleneimine. The process involves dispersing the NPZI in anhydrous ethanol and ultrasonically treating it for 10 minutes at 300W and 40kHz. The NPZI solution is then added, stirred at 50°C for 1 hour, and filtered, washed, and dried to obtain the modified NPZI. The weight-to-volume ratio of the NPZI to the ethanol is 1:8 (g / mL), and the concentration of the NPZI solution is 3wt%. The weight-to-volume ratio of the NPZI to the NPZI is 1:3 (g / mL).
[0078] The composite adsorbent is prepared by the following method:
[0079] B1. Attapulgite, activated carbon, carbon nanotubes, and starch were mixed and granulated by spray drying, and then calcined at 600° C. for 2 h to obtain a carrier material.
[0080] B2. Dissolve 4-carboxyphenylboronic acid in ethanol to obtain a 4-carboxyphenylboronic acid solution; immerse the support material in the 4-carboxyphenylboronic acid solution, stir and react at 65°C for 4 hours, then add sodium dithiocarbamate, stir and react at 80°C for 1.5 hours, filter, and wash to obtain an activated support.
[0081] B3. Pre-react polyethyleneimine with epoxy resin E-44 at 52°C for 1-1 h to obtain an imine bond prepolymer.
[0082] B4. Coat the imine bond prepolymer onto the activated support and cure at 85°C for 2h.
[0083] B5. Disperse the modified nano-zero-valent iron in deionized water to obtain a dispersion, then immerse the activated carrier in the dispersion, shake and absorb at room temperature for 2.5-3.5 hours, filter and separate, and dry the solid product at 80°C for 4 hours to obtain a composite adsorbent.
[0084] The gel microsphere oxidant is prepared by the following method:
[0085] C1. Under a nitrogen atmosphere, copper iron sulfide and nitrogen-doped carbon quantum dots were added to hydrogen peroxide precooled to 12°C. The mixture was ultrasonically dispersed at 36°C with an ultrasonic power of 400 W and an ultrasonic frequency of 25 kHz for 15 min. Phosphate buffer was added and stirred at 250 rpm for 4 min to obtain suspension I.
[0086] C2. Sodium alginate powder was added to suspension I, stirred at 160 rpm at 40°C for 25 min, then heated to 45°C and stirred at 85 rpm for 25 min. Potassium persulfate was added after cooling to 32°C, and magnetic stirring was performed at 500 rpm until completely dissolved to obtain viscous slurry II.
[0087] C3. The viscous slurry II was injected into a ball dropper, and a 2 wt% calcium chloride solution was added dropwise. The mixture was cured for 30 min to obtain microspheres. The microspheres were filtered out, washed with deionized water, and then freeze-dried at -40°C for 24 h to obtain a gel microsphere oxidant.
[0088] Comparative Example 1
[0089] Compared with Example 2, this comparative example differs in that unmodified nano-zero-valent iron is used in the composite adsorbent in step A2 instead of modified nano-zero-valent iron, that is, the nano-zero-valent iron is not modified.
[0090] Comparative Example 2
[0091] Compared with Example 2, this comparative example differs in that the composite adsorbent in step A2 includes the following raw materials in parts by weight: 50 parts of attapulgite, 25 parts of activated carbon, and 7.5 parts of carbon nanotubes. The composite adsorbent is prepared by the following method: attapulgite, activated carbon, and carbon nanotubes are mixed and calcined at a high temperature of 550°C for 2.5 hours to obtain the composite adsorbent.
[0092] Comparative Example 3
[0093] This comparative example is different from Example 2 in that an antioxidant is used in place of the gel microsphere oxidant in step A3. The antioxidant comprises the following raw materials in parts by weight: 55 parts of hydrogen peroxide and 22.5 parts of potassium persulfate.
[0094] Performance testing
[0095] 1. Heavy metal removal rate
[0096] Atomic absorption spectroscopy was used to measure the concentration of heavy metal ions in pharmaceutical wastewater before and after treatment, and the removal rate was calculated as: Removal rate (%) = (C0 - C1) / C0 × 100%, where C0 is the original concentration and C1 is the concentration after treatment. The test results are shown in Table 1.
[0097] 2. Suspended matter removal rate
[0098] The concentration of suspended solids in pharmaceutical wastewater before and after treatment was tested by drying and weighing method, and the suspended solids removal rate was calculated. The removal rate calculation method was the same as that for heavy metal detection. The test results are shown in Table 1.
[0099] 3. Organic matter removal rate
[0100] The biochemical oxygen demand (BOD5) method was used to detect the concentration of suspended solids in pharmaceutical wastewater before and after treatment, and the suspended solids removal rate was calculated. The removal rate calculation method was the same as that for heavy metal detection. The test results are shown in Table 1.
[0101] Table 1
[0102] Heavy metal removal rate% Suspended matter removal rate% Organic matter removal rate% Example 1 96.85 92.12 86.78 Example 2 97.89 94.25 87.91 Example 3 97.32 93.58 85.36 Comparative Example 1 92.45 91.03 80.56 Comparative Example 2 82.23 81.67 78.34 Comparative Example 3 86.32 83.54 79.12
[0103] As can be seen from Table 1, Examples 1-3 of the present invention achieved relatively high levels of heavy metal removal rate, suspended solids removal rate, and organic matter removal rate, and were superior to the comparative example. This indicates that the pharmaceutical wastewater treatment process of the present invention is highly efficient and stable and can be widely applied to pharmaceutical wastewater treatment in factories.
[0104] The composite adsorbent of the present invention significantly improves its ability to remove organic matter and heavy metals through a multi-mechanism of physical adsorption, chemical adsorption, and catalytic oxidation. Self-repair is achieved through dynamic chemical bonds such as borate bonds, imine bonds, and thiol-disulfide bonds. Specifically, 4-carboxyphenylboronic acid forms borate bonds (BOC) on the surface of the activated support. The borate bonds are pH-responsive and dynamically reversible. They can break and reform under pH changes. When microcracks or micropores form on the adsorbent surface due to physical wear or chemical corrosion, the borate bonds break under local pH fluctuations, releasing active functional groups. These functional groups then re-bind with adjacent hydroxyl groups (from attapulgite or carbon nanotubes) to form new borate bonds, filling the microcracks. The dynamic nature of the borate bonds enables the adsorbent to maintain structural integrity during multiple adsorption-desorption cycles, reducing performance degradation. The imine bonds formed by polyethyleneimine and epoxy resin are thermally reversible. Under the action of hot water, the imine bonds reversibly break, releasing free amino and aldehyde groups. These groups re-condense after cooling to form new imine bonds, repairing cross-linked network damage caused by thermal stress or chemical corrosion, thereby allowing the adsorbent to maintain a high adsorption capacity. The modified nano zero-valent iron generates precipitates such as FeO(OH) through reduction, filling surface cracks and inhibiting metal corrosion. A reversible chemical bond network is constructed through the synergistic effect of imine bonds (-C=N-) and disulfide bonds (-SS-). The pH-responsive recombination of imine bonds and the redox exchange mechanism of disulfide bonds enable the adsorbent to repair itself when microscopically damaged, thereby extending its service life. The modified nano zero-valent iron not only provides electrons to accelerate dynamic bond recombination, but also a space-filling effect to prevent crack propagation, realizing an integrated "catalysis-repair" design.
[0105] The gel microsphere oxidant of the present invention achieves efficient degradation through the synergistic mechanism of free radical oxidation + non-free radical oxidation + photocatalysis. Hydrogen peroxide decomposes under the catalysis of copper iron sulfide to produce hydroxyl radicals, while potassium persulfate generates sulfate radicals. The two work together to form a free radical chain reaction system, thereby enhancing the oxidation ability. Nitrogen-doped carbon quantum dots have excellent light absorption capacity and electron transfer characteristics, which can convert light energy into chemical energy, further activate hydrogen peroxide and potassium persulfate, and promote the generation of free radicals. The conduction band of copper iron sulfide matches the valence band of nitrogen-doped carbon quantum dots to form a Z-type heterojunction, which promotes the separation of photogenerated electrons and holes. The nitrogen atoms of nitrogen-doped carbon quantum dots act as active sites, adsorbing persulfate and reducing its decomposition energy barrier. In addition, the sulfur vacancies on the surface of copper iron sulfide adsorb pollutant molecules through coordinated unsaturated sites to achieve targeted oxidation. -COO of sodium alginate - -COO with sodium polyacrylate - The porosity inside the microspheres is increased by forming an interpenetrating network through electrostatic interaction.
[0106] This solution breaks through the bottleneck of traditional pharmaceutical wastewater treatment technology by combining material innovation with process optimization, achieving significant improvements in efficiency and environmental performance. It has outstanding practical value and industry promotion potential.
[0107] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A pharmaceutical wastewater treatment process, characterized in that: The following steps are involved: A1. Pretreatment: Pharmaceutical wastewater is introduced into a regulating tank and adjusted to a pH of 5.0-6.
0. The regulated wastewater then enters a coagulation and sedimentation tank. After adding a coagulant, the wastewater is aerated and stirred for 2-3 hours, and then allowed to settle for 18-24 hours. A2. Adsorption: The pretreated supernatant was passed through a fixed-bed reactor filled with a composite adsorbent at a flow rate of 4-5 L / min for adsorption. The composite adsorbent ingredients included attapulgite, activated carbon, carbon nanotubes, starch, sodium dithiocarbamate, 4-carboxyphenylboronic acid, epoxy resin E-44, polyethyleneimine, modified nano-zero-valent iron, and deionized water. A3. Oxidation treatment: The wastewater after adsorption treatment is passed into the oxidation tank, and the gel microsphere oxidant is added at a dosage of 200-300 mg / L, and the aeration reaction is carried out for 1-2 hours; A4. Filtration treatment: The wastewater after oxidation treatment is filtered through an activated carbon filter with a residence time of 15-30 minutes to obtain purified water.
2. A pharmaceutical wastewater treatment process according to claim 1, characterized in that: The coagulant described in A1 is composed of polyaluminium chloride and aluminium sulfate in a mass ratio of (5-7):(3-5).
3. A pharmaceutical wastewater treatment process according to claim 1, characterized in that: The regulator for regulating the pH of pharmaceutical wastewater in A1 is a hydrochloric acid solution with a mass concentration of 10-20wt%.
4. A pharmaceutical wastewater treatment process according to claim 1, characterized in that: The composite adsorbent in A2 comprises the following raw materials in parts by weight: 40-60 parts of attapulgite, 20-30 parts of activated carbon, 5-10 parts of carbon nanotubes, 2-5 parts of starch, 10-15 parts of 4-carboxyphenylboric acid, 20-30 parts of polyethyleneimine, 5-8 parts of sodium dithiocarbamate, 5 parts of epoxy resin E-443, 50-80 parts of deionized water, and 10-15 parts of modified nano zero-valent iron; The modified nanometer zero-valent iron is obtained by coating the nanometer zero-valent iron with polyethyleneimine through chemical bonding.
5. A pharmaceutical wastewater treatment process according to claim 1, characterized in that: The modified nano-zero-valent iron is prepared by the following method: dispersing the nano-zero-valent iron in anhydrous ethanol, ultrasonically treating it for 10-20 minutes under ultrasonic power of 100-300W and ultrasonic frequency of 20-40kHz, then adding polyethyleneimine solution, stirring and reacting at 30-50°C for 1-2 hours, filtering, washing, and drying to obtain the modified nano-zero-valent iron.
6. A pharmaceutical wastewater treatment process according to claim 5, characterized in that: The mass volume ratio of the nano zero-valent iron to anhydrous ethanol is 1:(5-8) g / mL, the mass concentration of the polyethyleneimine solution is 3-5wt%; the mass volume ratio of the polyethyleneimine solution added to the nano zero-valent iron is 1:2-3 g / mL.
7. A pharmaceutical wastewater treatment process according to claim 4, characterized in that: The composite adsorbent is prepared by the following method: B1. The attapulgite, activated carbon, carbon nanotubes and starch were mixed and granulated by spray drying and calcined at 500-600 ℃ for 2-3h to obtain a carrier material; B2. 4-carboxyphenylboronic acid was dissolved in ethanol to obtain a 4-carboxyphenylboronic acid solution; the support material was immersed in the 4-carboxyphenylboronic acid solution, stirred at 55-65 ° C for 4-6h, followed by the addition of sodium dithiocarbamate, stirred at 70-80 ° C for 1.5-2.5h, filtered and washed to obtain an activated support; B3. Pre-react polyethyleneimine with epoxy resin E-44 at 48-52 ° C for 1-1.5h to obtain an imine bond prepolymer; B4. The imine bond prepolymer is coated onto the activated support and cured at 75-85°C for 2-3h; B5. Disperse the modified nano-zero-valent iron in deionized water to obtain a dispersion, then immerse the activated support in the dispersion. Oscillate and adsorb at room temperature for 2.5-3.5 hours. After filtration and separation, the solid product is dried at 60-80°C for 4-6 hours to obtain a composite adsorbent.
8. A pharmaceutical wastewater treatment process according to claim 1, characterized in that: The gel microsphere oxidant described in A3 includes the following raw materials in parts by weight: 50-60 parts of hydrogen peroxide, 20-25 parts of potassium persulfate, 10-15 parts of copper iron sulfide, 4-8 parts of nitrogen-doped carbon quantum dots, 8-12 parts of sodium alginate powder, 0.5-1 part of sodium polyacrylate, and 0.8-1.2 parts of phosphate buffer.
9. A pharmaceutical wastewater treatment process according to claim 8, characterized in that: The gel microsphere oxidant is prepared by the following method: C1. Under a nitrogen atmosphere, copper iron sulfide and nitrogen-doped carbon quantum dots were added to hydrogen peroxide precooled to 8-12°C. The mixture was ultrasonically dispersed at 34-36°C for 15-20 minutes. Phosphate buffer was added and stirred for 4-6 minutes to obtain suspension I. C2. Sodium alginate powder was added to suspension I, stirred at 40°C at 140-160 rpm for 25-30 min, then heated to 45°C at 75-85 rpm for 25-30 min, cooled to 30-32°C, potassium persulfate was added, and magnetic stirring was performed until completely dissolved to obtain a viscous slurry II; C3. The viscous slurry II was injected into a ball dropper, and 2 wt% calcium chloride solution was added dropwise. The mixture was cured for 20-30 min to obtain microspheres. The microspheres were filtered out, washed with deionized water, and then freeze-dried to obtain a gel microsphere oxidant.
10. A pharmaceutical wastewater treatment process according to claim 9, characterized in that: In C1, the ultrasonic power is 200-400W, the ultrasonic frequency is 15-25kHz, and the stirring speed is 150-250rpm. In C2, the magnetic stirring speed is 300-500rpm. In C3, the freeze-drying temperature is -30 to -40°C, and the drying time is 24-36h.
Citation Information
Patent Citations
Composite wastewater treatment adsorbent and preparation method thereof
CN106186169A
Chemical precipitation-adsorption method combined industrial wastewater treatment method
CN113023932A
Cited By
Cyclohexanol dehydrogenation cyclohexanone catalyst and preparation method thereof
CN120861064A
Catalyst for preparing cyclohexanone by dehydrogenation of cyclohexanol and its preparation method
CN120861064B